Microstructure and Chemistry of Electrodeposited Mg Films. Issue 13 (1st January 2016) - Bachhav, Mukesh N.; Hahn, Nathan T.; Zavadil, Kevin R.; Nelson, Emily G.; Crowe, Adam J.; Bartlett, Bart M.; Chu, Peng-Wei; Araullo-Peters, Vicente J.; Marquis, Emmanuelle A.
Abstract : We describe the structure, morphology, and chemistry of Mg films that were electrodeposited using different electrolytes (magnesium aluminum chloride complex (MACC), magnesium bis(trifluoromethylsulfonyl)imide (Mg-TFSI) and magnesium triphenoxyaluminate (MTPA)). The microstructure and chemistry of the Mg films, along with their overall cycling efficiency, showed a strong dependence on electrolyte chloride content. The films formed with the higher chloride concentration electrolytes (MACC and MTPA) yielded large and columnar grain structures with a strong [001] texture. The films formed using chloride-free TFSI that only has an 80% cycling efficiency showed much smaller grains and a more random texture. Electrochemically conditioned MACC and MTPA also led to smaller amounts of impurity being incorporated in the films than TFSI. The impurities detected in the form of Mg complexes such as Mg-O, Mg-H, Mg-OH, Mg-C, and elemental impurities (O, C, Cl, Al) tend to form discontinuous films orthogonal to the [001] direction.